Analysis of The Acceleration of Time and Cost of Construction Projects by Adding Labor and Working Hours (Overtime) using The Time Cost Trade Off Method (Case study: Construction of The Conexio Apartment Project) - Hamonangan Girsang; M. Andi Wahyud (Journal of World Conference (JWC), 2021)
Systematic project management is needed to ensure the project implementation time is in accordance with the contract or even faster, so the cost incurred can provide benefits and also avoid the existence of fines due to delays in project completion. This study discusses the acceleration of time and cost project in the implementation of high rise building construction projects using the Time Cost Trade Off method. The author will analyze the scenario of accelerating the completion of the project by comparing the addition of working hours by 4 hours (scenario 1) and additional labor (scenario 2). The results of the analysis found the estimated time to accelerate the implementation of the project is from the normal duration of 600 calendar days, after a crash duration there is an acceleration of time to 582 calendar days. With a time efficiency of 18 days / 3.00%. The total cost due to acceleration of time (including indirect cost) for the addition of overtime hours for 4 hours (scenario 1) obtained a normal cost of IDR 66,637,746,719 (excl. VAT), then after the crash cost there is an increase in the cost to IDR 70,224,661,008 (excl. VAT) with an over cost of IDR 3,586,914,289 / 5.38%. Whereas with the addition of labor (scenario 2) a normal cost of IDR 66,637,746,719 (excl. VAT), then after the crash cost there is an increase in the cost to IDR 71,454,128,134 (excl. VAT) with an over cost of IDR 4,816,381,415 / 7.23%.